The darkness of the present : poetics, anachronism, and the anomaly - McCaffery, Steve (University of Alabama Press, 2012)
This book includes essays that collectively investigate the roles of anomaly and anachronism as they work to unsettle commonplace notions of the "contemporary" in the field of poetics. In this book, a poet and critic argues that by approaching the past and the present as unified entities, the contemporary is made historical at the same time as the historical is made contemporary.
Keywords: Poetics.; Literature -- Philosophy.; Poétique.; LITERARY CRITICISM -- Poetry.; Literature -- Philosophy; Poetics; Electronic book.